Nigella Sativa's Anti-Inflammatory and Antioxidative Effects in Experimental Inflammation - Raluca Maria Pop; Octavia Sabin; Șoimița Suciu; Stefan Cristian Vesa; Sonia Ancuța Socaci; Veronica Sanda Chedea; Ioana Corina Bocsan; Anca Dana Buzoianu (MDPI AG, 2020)
Nigella sativa (NS) has been used for centuries in various inflammatory conditions because of its anti-inflammatory and antioxidant activities. The study aimed to evaluate the anti-inflammatory, antinociceptive and antioxidant activity of Nigella sativa oil (NSO) in two models of acute (carrageenan-induced) and sub-acute inflammation (complete Freund's adjuvant induced) in rats. Materials and Methods: NSO was administered orally 1, 2 and 4 mL/kg in the acute phase. For subacute phase, NSO was administered 4 mL/kg, 7 days before or after inflammation induction, or in association with diclofenac 5 mg/kg. Results: The gas chromatography coupled with mass spectroscopy (GC-MS) analysis showed that NSO is an important source of bioactive compounds, especially p-cymene and thymoquinone. In the acute phase, 1.5 h after administration, NSO (2 and 4 mL/kg) determined an anti-inflammatory effect comparable with that of diclofenac. In the sub-acute administration, NSO had no anti-inflammatory effect. The analgesic effect of NSO was observed only in the sub-acute inflammation in the analgesy-meter test. NSO as treatment proved its antioxidant effect through the reduction of malondialdehyde (MDA) and oxidized glutathione (GSSG), and increases in hydrogen donor capacity (DH) compared to the control group, but the effect was not as intense as that of diclofenac. Conclusion: The present study has proven inconstant anti-inflammatory, analgesic and antioxidative properties of NSO.